Effects of added choline on performance of weanling pigs - Hongtrakul, K.; Kim, I.H.; Loughmiller, J.A.; Smith, J.W.; Cao, H.; Goodband, Robert D.; Tokach, Michael D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A 28-d growth assay was conducted to determine the effects of added choline on weanling pig performance. Pigs were fed a control diet without added choline or diets containing 150 g/ton of added choline. No differences in pig growth performance were observed. These results suggest that added choline can be removed from weanling pig diets.
Keywords: Swine; Weanling pigs; Choline